Transcriptional analyses of two soybean cultivars under salt stress - Cadavid, Isabel Cristina (2020)
Soybean is an economically important plant, and its production is affected in soils with high salinity levels. It is important to understand the adaptive mechanisms through which plants overcome this kind of stress and to identify potential genes for improving abiotic stress tolerance. RNA-Seq data of two Glycine max cultivars, a drought-sensitive (C08) and a tolerant (Conquista), subjected to different periods of salt stress were analyzed. The transcript expression profile was obtained using a transcriptogram approach, comparing both cultivars and different times of treatment. After 4 h of salt stress, Conquista cultivar had 1400 differentially expressed genes, 647 induced and 753 repressed. Comparative expression revealed that 719 genes share the same pattern of induction or repression between both cultivars. Among them, 393 genes were up- and 326 down-regulated. Salt stress also modified the expression of 54 isoforms of miRNAs in Conquista, by the maturation of 39 different pre-miRNAs. The predicted targets for 12 of those mature miRNAs also have matches with 15 differentially expressed genes from our analyses. We found genes involved in important pathways related to stress adaptation. Genes from both ABA and BR signaling pathways were modulated, with possible crosstalk between them, and with a likely post-transcriptional regulation by miRNAs. Genes related to ethylene biosynthesis, DNA repair, and plastid translation process were those that could be regulated by miRNA.